Penyusunan E-Modul Sejarah Tentang Penyebaran Islam di Nusantara untuk Siswa Kelas X SMK Surya Dharma Bandar Lampung Tahun Pelajaran 2024/2025 - Nandia Febrianti, Aurora; Ciciria, Deri; Azmi Muhammad, Ulul; Yudhistira, Ardhi; Ageng Kurniawan, Amar (Universitas Batanghari Jambi, 2024)
The use of appropriate media, especially in history learning, is very important to improve student learning outcomes. The results of interviews with teachers showed that the limitations of learning media cause students to tend to be passive and have poor understanding of the material. Therefore, the E-Module is designed to provide opportunities for students to learn independently with interesting and easy-to- understand material. The research method used in this study is the Research and Development (R&D) method with the ADDIE approach which contains analysis, design, development, implementation, and evaluation. The purpose of this study was to test the effectiveness of the E-Module for history learning. After conducting the research, it can be concluded that the E-Module developed has a very high level of validity, with validation results from material experts of 95%, language experts of 92%, and media experts of 97%. This module has also proven effective with student response percentage results of 96% and teacher responses of 97%. This History Learning E-Module achieved learning outcomes of 88%. This E-Module is expected to improve students' understanding and learning outcomes of history, as well as facilitate more interactive and independent learning.